T17. ACUTE CONCEPTUAL DISORGANIZATION IN UNTREATED FIRST-EPISODE PSYCHOSIS: A 7T DTI STUDY OF CINGULUM TRAC - Pan, Yunzhi (Schizophr Bull, 2019)
BACKGROUND: The structural integrity of the anterior cingulum has been repeatedly observed to be abnormal in psychosis. Cingulum tract carries fibers that connect medial prefrontal structures with precuneus, thus serving as the major pathway within the default mode network (DMN), critical for self-related processing. Persistent disorganization (or formal thought disorder) is largely considered to be a language-related dysfunction, though the neural basis of acute disorganization is yet unknown. We studied bilateral cingulum tract to identify if fractional anisotropy (indicating reduced white matter integrity) differed between patients with high vs. low levels of conceptual disorganization at first presentation, before initiating treatment. METHODS: We used ultra-high resolution (7 Tesla) diffusion weighted imaging in 40 patients with first-episode psychosis and 25 controls, to investigate bilateral cingulum, defined according to JHU white matter atlas. Based on the conceptual disorganization scores of PANSS, we divided patients in to 2 groups, low (P2=1,2,3) and high (P2=4,5,6) groups. These two groups were not different in their severity of other positive and negative symptoms. TBSS was applied to compare fractional anisotropy (FA) values using FSL software and permutation (5000) correction was used within the selected tract. F tests were used for group comparisons. We undertook post-hoc comparisons of radial diffusivity (reflecting myelin content), axial diffusivity (reflecting axonal integrity) and mode of anisotropy (reflecting fiber organization) for the regions showing significant FA abnormalities. RESULTS: There was a significant reduction in FA (p=0.036) in a cluster in left cingulum, with high P2 groups showing lower values than low P2 and controls. Post hoc showed that high P2 group had lower AD values compared to low P2 group (P=0.021). Interestingly, we also noted that patients with low P2 group had significantly higher AD values than healthy controls, indicating resilience from disorganization conferred by increased cingulum integrity. We did not find any significant difference in RD and MO value among the 3 groups. These FA differences were not explained by the distribution of other symptom scores. DISCUSSION: Our findings suggest that acute conceptual disorganization may relate to white matter damage of cingulum, the microstructural organization of which is critical for functional synchronization within the default mode network. We propose that the neural correlates of acute conceptual disorganization may differ from those of chronic, persistent formal thought disorder, in that language areas are less likely to be involved in acute disorganization.